Comparison of three flap designs on postoperative complication after third molar surgery - Pingky Krisna Arindra; Adyaputra Indrapradana (Intisari Sains Medis, 2018)
Introduction: Third molar surgery can cause post-operative complications to the patient due to the presence of wound from the incision. The study aimed to compare modified triangular (triangular reverse) flap with triangular and envelope flap on postoperative complications by the measurements on post-surgical swelling, trismus, pain scale, wound dehiscence and the occurrence of alveolar osteitis.Methods: Study design using a single-blind randomized clinical trial. Each treatment group consisted of 10 patients. An assessment was performed on day 1, 7 and 14 after surgery. The swelling was measured using different anatomical points, and trismus was measured using the distance of inter-incisal opening. The occurrence of dehiscence was measured from the width of the incision line. Alveolar osteitis and pain scale was observed.Results: The results of one way ANOVA (p>0.05) shows there was no difference between treatment groups both for swelling and mouth opening, but there was a difference between treatment groups for dehiscence on days 7 and 14. The results of the Post Hoc test show that flap envelope differs from the other flap design, whereas triangular and triangular reverse flap showed no difference. Friedman test results (p>0.05) showed no difference in VAS score. There was no alveolar osteitis occurred in each treatment group during postoperative control. Kruskal Wallis test (p>0.05) showed that there was no difference of VAS score between treatment group during post-operative control.Conclusion: The triangular reverse flap design may decrease the occurrence of postoperative complication after mandibular third molar surgery.Â